2020
DOI: 10.1039/c9mh01215j
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous polarization switching and permanent retention in a ferroelectric ionic conductor

Abstract: Ionic conduction in a ferroelectric leads to anomalous polarization switching kinetics but prevents retention failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
121
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 89 publications
7
121
1
Order By: Relevance
“…[28] In addition, CIPS has a high Cu-ion conductivity that extends into the temperature range of the ferroelectric phase. [30][31][32] It has been shown that in-plane ionic currents can be used to manipulate ferroelectric polarization. [33] These highly unusual properties that are rooted in the vdW structure provide the opportunity for complex polarization switching which might be exploited in transient-NC devices beyond the mechanisms discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…[28] In addition, CIPS has a high Cu-ion conductivity that extends into the temperature range of the ferroelectric phase. [30][31][32] It has been shown that in-plane ionic currents can be used to manipulate ferroelectric polarization. [33] These highly unusual properties that are rooted in the vdW structure provide the opportunity for complex polarization switching which might be exploited in transient-NC devices beyond the mechanisms discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…This article also can be found at http://journal.hep.com.cn/fop/EN/10.1007/s11467-020-0998-9 layer lead to exotic negative piezoelectricity, which is the second experimentally confirmed one (and the first in inorganic materials) [5]. Also, thanks to the high mobility of small copper ions and loose framework, the ionic conduction is prominent in this system [7], an uncommon property for ferroelectric materials and important for ionic battery applications.…”
mentioning
confidence: 65%
“…Recently CuInP 2 S 6 (CIPS), a typical room-temperature van der Waals (vdW) layered ferroelectric crystal 19,20,21 , has attracted intensive attention due to its unexpected features including giant negative piezoelectricity 22 , tunable quadruple-well ferroelectric nature 23 , negative capacitance characteristic 24 and the interplay between ferroelectricity and ionic conductivity 25,26,27 . These unique characteristics not only bring new insights into the fundamental research 28,29 , but also provide new opportunities for diverse applications of layered ferroelectrics 30,31 .…”
Section: Introductionmentioning
confidence: 99%